2016
DOI: 10.1080/09585176.2016.1174140
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the suitability of mathematical thinking problems for senior high‐school students by including mathematical sense making and global planning

Abstract: To cite this article: Joke H. van Velzen (2016) Evaluating the suitability of mathematical thinking problems for senior high-school students by including mathematical sense making and global planning, The Curriculum Journal, 27:3, 313-329, DOI: 10.1080/09585176.2016 ABSTRACTThe mathematics curriculum often provides for relatively few mathematical thinking problems or non-routine problems that focus on a deepening of understanding mathematical concepts and the problem-solving process. To develop such problems… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Studies measuring students' mathematical thinking skills found that secondary school students were good at mathematical thinking (Akçakın & Kaya, 2020;Arslan & Yıldız, 2010;Göl, 2017;Kocaman, 2017). Similarly, studies conducted abroad reported that secondary school students had high mathematical thinking skills (Cortez, Cuevaz, & Castillo, 2019;Gine, 2010;Lutfiyya, 1998;Mashaqbah, 2017;Mustafa, Sari, & Baharullah, 2019;van Velzen, 2016). Lastly, various studies have measured secondary school students' scientific thinking skills.…”
Section: Discussion Regarding the First Research Questionmentioning
confidence: 99%
“…Studies measuring students' mathematical thinking skills found that secondary school students were good at mathematical thinking (Akçakın & Kaya, 2020;Arslan & Yıldız, 2010;Göl, 2017;Kocaman, 2017). Similarly, studies conducted abroad reported that secondary school students had high mathematical thinking skills (Cortez, Cuevaz, & Castillo, 2019;Gine, 2010;Lutfiyya, 1998;Mashaqbah, 2017;Mustafa, Sari, & Baharullah, 2019;van Velzen, 2016). Lastly, various studies have measured secondary school students' scientific thinking skills.…”
Section: Discussion Regarding the First Research Questionmentioning
confidence: 99%
“…Three of components EF are equal each other (Miyake, et al, 2000) and play an important role to multi-step strategy of mathematical word problem solving. In the other side, planning, monitoring and procedural are components in using strategy to solve mathematical word problem (van Velzen, 2016). In other words, how to solve mathematical word problem depend on working memory, inhibitory control and shifting flexibility.…”
Section: Introductionmentioning
confidence: 99%
“…Mathematics teachers would like to see learners engage in mathematical sense-making. The term 'sense-making' is often interwoven with ideas of deepening understanding and application of mathematical concepts (Van Velzen, 2016). This article uses a conceptual approach to explore learner choice as a property of sense-making.…”
Section: Introductionmentioning
confidence: 99%
“…of Teachers of Mathematics (NCTM) defined sensemaking more generally as 'developing understanding of a situation, context, or concept by connecting it with existing knowledge' (NCTM, 2016, p. 1). Sense-making is more about flexible application of mathematical knowledge(Van Velzen, 2016) than it is about performing procedures.http://www.pythagoras.org.zaOpen Access…”
mentioning
confidence: 99%